2018
DOI: 10.1093/rpd/ncx293
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of Adult and Pediatric Patients for Common Digital Radiography Examinations

Abstract: The present work reports dosimetry data on adult and pediatric patients for some common radiographic examinations during the standard hospital routine. The measurements are the part of quality assurance program to determine radiation exposures to patients in these examinations. The entrance skin doses (ESDs) of the patients were measured from 2451 projection for 12 diagnostic examinations in digital radiography (DR). The ESDs in adult patient were measured using thermoluminescence dosemeters placed on the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…This reduction in patient dose by using flat panel detectors is also reported by Sjoholm et al, and Metaxas et al, (Sjöholm, 2005;Metxas, 2019). Comparing present study results with similar study in India by Bhupinder et al, it is observed that for skull Lat the percentage decrease of radiation dose is found to be 86% (Rana et al, 2018). The mean patient weight of both the studies is comparable.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This reduction in patient dose by using flat panel detectors is also reported by Sjoholm et al, and Metaxas et al, (Sjöholm, 2005;Metxas, 2019). Comparing present study results with similar study in India by Bhupinder et al, it is observed that for skull Lat the percentage decrease of radiation dose is found to be 86% (Rana et al, 2018). The mean patient weight of both the studies is comparable.…”
Section: Resultssupporting
confidence: 82%
“…Demographic information and technical parameters are presented in Table 1. review (Rana, 2018;Uniyal, 2017;. Table 3 presents the effective doses its comparison with mean doses of UK 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2: Presents ESAK, PKA, and effective dose values obtained in this study (mean ±SD, median, 25 th , and 75 th percentile values). Table 3 [10][11][12][13]20 For chest PA, the percentage decrease of radiation dose is found to be 15%, 56%, 60% 29% with Suliman, Bhupendra et al, Satish et al, and Marco et al respectively. 10,11,13,20 The LDRLs reported by Suliman and Bhupendra et al are in digital radiography.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies aiming to investigate local radiographic practices in digital radiography are limited. 10,11 Features associated with DR like post-processing and large dynamic range can influence the contrast and density of image and can result in overexposures without the knowledge of the operator. 12,13 Present study aims to examine the current state of radiographic practice in chest digital radiographic examinations in a public teaching hospital in Delhi, India.…”
Section: Introductionmentioning
confidence: 99%
“…6 Any increase in tube voltage must be followed by a reduction in tube current and irradiation time so that the appropriate radiation intensity to produce a sufficient image quality is employed. [7][8][9] The patient dose in a DR examination is an issue highlighted by the Nuclear Energy Regulatory Agency of Indonesia (BAPETEN) and the Indonesian Hospital Accreditation Committee (KARS). The BAPETEN has published a webbased application for recording patient data called SI INTAN, and has established diagnostic-reference levels (DRL) for all diagnostic radiography.…”
Section: Introductionmentioning
confidence: 99%